Agricultural, fishery, food and sustainable rural development in Greece - Kagkou E. (Les agricultures méditerranéennes : analyses par pays, 2008)
Economic developments in 2006 are characterised by strong real GDP growth, significant increases in investment and growth in exports of goods, and a reduction of the fiscal deficit, reaching levels below the threshold value of 3 percent of GDP. But if long-run fiscal sustainability is to be attained, wide-ranging reforms are needed. The farm profile can be described as that of many small farms with a few small plots in less favoured areas: 76 percent of farms are less than 5 ha and only 1 percent is larger than 50 ha; 71 percent of farms are situated in hilly and mountainous, or less favoured areas. The small size of farms, the high average age of the farmer and low educational attainment are important impediments to improving the sector’s productivity. In 2006, the value of agricultural output in real terms declined, food prices rose slightly higher than the inflation rate and real agricultural income per person increased. The food processing sector has become more concentrated, while aquaculture is increasing rapidly. Implementation of the 2003 CAP reform in Greece took the form of full decoupling of support for all products except for seeds (where payments remain fully linked to production) and cotton (where payments are partially coupled to cotton production). Farmers will receive compensation for damages caused by the catastrophic forest fires occurred in summer 2007.